Design of a passive rainwater harvesting system with green building approach - Elif Kucukkaya; Alper Kelesoglu; Hira Gunaydin; Gulenay A. Kilic; Umit Unver (International Journal of Sustainable Energy, 2021)
In this study, a passive rainwater harvesting system was designed. The system is planned to be installed on the roof of the building of Engineering Faculty of Yalova University. The meteorological rain data of Yalova province was analysed and the most suitable rainwater silo dimensions were determined accordingly. A suitable location for the silo was recommended considering the statics of the building. The passive rainwater harvesting system requires no additional pump power and no complex filtration systems. A rainwater delivery system is designed from the roof to the reservoirs for flushing without any additional energy consumption according to the storage location. The minimum height between the tank and the floor was determined to compensate the pressure losses along the critical length. The results of the economic analysis showed that this system can save about 8.5 tons of water/year and 2900 €/year water costs from one building.